Hsa_circ_0074491 regulates the malignance of cholesteatoma keratinocytes by modulating the PI3K/Akt pathway by binding to miR-22-3p and miR-125a-5p: An observational study. Issue 37 (17th September 2021) - Hu, Yunlong; Qian, Xudong
Abstract : Abstract: Cholesteatoma is a benign cystic lesion that can continue to grow like a tumor. Circular ribonucleic acid (RNA) hsa_circ_0074491 (circ_0074491) has been reported to be down-regulated in cholesteatoma tissues. However, the role and regulatory mechanism of circ_0074491 in the growth of cholesteatoma are unclear. The expression of circ_0074491, microRNA (miR)-22-3p, and miR-125a-5p in cholesteatoma tissues was detected by quantitative real-time polymerase chain reaction. The proliferation, cell cycle, apoptosis, migration, and invasion of cholesteatoma keratinocytes were evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide, plate clone, flow cytometry, or transwell assays. Several protein levels were examined by western blotting. The targeting relationship between miR-22-3p or miR-125a-5p and circ_0074491 was verified via dual-luciferase reporter and RNA pull-down assays. We observed the downregulation of circ_0074491 in cholesteatoma tissues. Furthermore, circ_0074491 knockdown facilitated cell proliferation, migration, invasion, and repressed cell apoptosis in cholesteatoma keratinocytes. Circ_0074491 was verified as a decoy for miR-22-3p and miR-125a-5p in cholesteatoma keratinocytes. Both miR-22-3p and miR-125a-5p silencing reversed the impacts of circ_0074491 silencing on proliferation, apoptosis, migration, and invasion of cholesteatoma keratinocytes. Also, circ_0074491 knockdown activated the PI3K/Akt pathway in cholesteatoma keratinocytes via miR-22-3p and miR-125a-5p. Circ_0074491 played a suppressive role in cholesteatoma through inactivating the PI3K/Akt pathway via binding to miR-22-3p and miR-125a-5p, which provided a novel evidence for the involvement of circRNA in the development of cholesteatoma.